X‐ray Nano‐computed Tomography of Electrochemical Conversion in Lithium‐ion Battery. Issue 15 (16th July 2019) - Di Lecce, Daniele; Levchenko, Stanislav; Iacoviello, Francesco; Brett, Dan J. L.; Shearing, Paul R.; Hassoun, Jusef
Abstract: Herein, a nanometric CuO anode for lithium‐ion batteries was investigated by combining electrochemical measurements and ex situ X‐ray computed tomography (CT) at the nanoscale. The electrode reacted by conversion at about 1.2 and 2.4 V versus Li + /Li during discharge and charge, respectively, to deliver a capacity ranging from 500 mAh g −1 to over 600 mAh g −1 . Three‐dimensional nano‐CT imaging revealed substantial reorganization of the CuO particles and precipitation of a Li + ‐conducting film suitable for a possible application in the battery. A lithium‐ion cell, exploiting the high capacity of the conversion process, was assembled by using a high‐performance LiNi0.33 Co0.33 Mn0.33 O2 cathode reacting at 3.9 V versus Li + /Li. The cell was proposed as an energy‐storage system with an average working voltage of about 2.5 V, specific capacity of 170 mAh gcathode −1, and efficiency exceeding 99 % with a very stable cycling. Abstract : Peering into and through : X‐ray computed tomography is used to shed light on the electrochemistry of CuO at the nanoscale, involving nanoparticle reorganization and precipitation of a passivation layer. A CuO/LiNi0.33 Co0.33 Mn0.33 O2 cell delivering almost 170 mAh gcathode −1 at 2.5 V suggests a possible application of nanometric metal oxides as anodes for lithium‐ion batteries.